The Perception Of Class VII Students On Classical Assistance Services At SMP Negeri 26 Padang - Intan Verly Syafitri; Yusri Yusri (Jurnal Neo Konseling, 2021)
Ideally, classical counseling is carried out so that students are active, creative and enthusiastic in the learning process according to the demands of the 2013 curriculum. In fact, counseling teachers still provide services using the lecture method, so students go in and out of learning, lie down, talk to friends and others. From interviews with counseling teachers, counseling teachers often perceive the provision of classical services by students as boring and useless lectures, and many students are not interested in taking classical services. The purpose of this study was to see how "Perceptions of Class VII Students Against Classical Guidance Services at SMP Negeri 26 Padang". This type of research is a descriptive study using quantitative methods. The population of this research was 239 students of class VII at SMP Negeri 26 Padang, and the sample of this research was 149 students who were selected by using proportional random sampling technique. Collecting data using a questionnaire about the perceptions of grade VII students towards classical guidance services at SMP Negeri 26 Padang Likert scale model. Data analysis using the percentage formula. The results of the study revealed that: (1) The opening of services by BK teachers was in the very good category. (2) The use of methods by BK teachers is in the good category. (3) The use of media by BK teachers is in the good category. (4) Guidance for counseling teachers is in the good category. (5) Conducting evaluation by BK teachers is in the very good category. (6) The time spent by counseling teachers is in the poor category. Based on the findings of this study, it is hoped that guidance and counseling teachers should be able to improve the quality of performance by being more creative and innovative in opening services, methods, media, service materials, evaluation and service time to better suit student needs.